Tensors and their applications - Islam, Nazrul (New Delhi: New Age International, 2006)
Reading books is a kind of enjoyment. Reading books is a good habit. We bring you a different kinds of books. You can carry this book where ever you want. It is easy to carry. It can be an ideal gift to yourself and to your loved ones. Care instruction keep away from fire.
Index 243-245p.
Keywords: Tensors; Mathematics